Colonial displacement of traditional fisheries management: Consequences of food-insecurity, perceptions, & stewardship practices in indigenous salmon fisheries: A case study for Heiltsuk Nation - Steel, Jade Ryan, 1994- (2020)
Verkefnið er lokað til 30.06.2021. Currently in Canada, colonial fisheries management practices are dysfunctional in regards to co-management, and are not equitable in relation to Indigenous communities who have relied on salmon since time before memory. By shifting salmon harvests to more costly marine fishing methods and eliminating traditional communal fisheries, colonial governments have reduced access to salmon amongst First Nations communities, threatening the cultural transmission of stewardship knowledge and undermining food security for coastal Indigenous peoples. In the last ~50 years, scientific and technological advances have made it possible to successfully monitor salmon abundance, and population structures, however, despite these advances, declining salmon abundance is currently a problem affecting most wild salmon regions around the globe. In Bella Bella, British Columbia there is currently a lack of baseline information regarding salmon run timing, stock-specific harvest rates, population status, as well as understandings of Indigenous perceptions towards the salmon fishery and its overall equity. This thesis aimed to identify, understand, and quantify the impacts of colonial management on the Food, Social, and Ceremonial salmon fishery for the Heiltsuk Nation. In addition, this thesis documents and evaluates current perceptions of the overall equity and sustainability of the salmon Food Social and Ceremonial fisheries. Results from this study highlight the continued importance of salmon use for First Nations in British Columbia as well as the economic significance, overall well-being, and self identification that comes with the utilization of salmon. Additionally, it was indicated that Heiltsuk people are frequently unable to meet their needs in regards to salmon, creating mounting pressure for improvement to the current management systems governing access and opportunity in wild salmon fisheries in British Columbia. One promising avenue for transformation can be found in efforts to restore ...